Algoritmo matemático de la separación de un sistema binario mediante electrodiálisis (2017)
Electrodialysis is a used separation technique for water desalination and recovery of salts, acids and aqueous mixtures bases. This paper aims to implement a mathematical model using theoretical models and simplifications, can represent a separation by electrodialysis for a binary aqueous solution. Equations raised model phenomena mass transfer occurring along the electrodialysis module considering some simplifying assumptions in order to facilitate the modeling process. The model also contains equations describing energy consumption of the separation, which, along with the purity obtained for the solute, allows to estimate the viability of the technique.